Presenteeism in the elite sports workplace: The willingness to compete hurt among German elite handball and track and field athletes - Mayer, J.; Thiel, A. (International Review for the Sociology of Sport, 2018)
Playing hurt is a widespread phenomenon in elite sports that often goes along with using painkillers, disregarding medical guidelines, and hiding pain from coaches, teammates and medical staff. This paper theoretically conceptualizes the phenomenon of playing hurt as a sport-specific sickness presenteeism problem. To empirically analyse the willingness to play hurt, we refer to survey data from 723 elite German athletes, both male and female, in the sports of handball and track and field. Factor analysis, cluster analysis and binary logistic regression analysis are applied to reveal the athletes` cognitive representation of absence legitimacy and to identify athlete groups with varying levels of willingness to compete hurt. Our results show that subtle distinctions are made between different kinds of health problems. In particular, there is a high willingness to compete despite psychosocial complaints. Cluster analysis reveals two clusters: `athletes conditionally willing to rest` and `rest-averse and pain-trivializing athletes`. Athletes who perceive more social pressure to compete hurt, who have a higher performance level and who participate in handball, are more likely to be in the group of rest-averse and pain-trivializing athletes. The findings enhance our understanding of presenteeism and absenteeism in a highly competitive work context, and can contribute to the development of more target-group-specific health prevention programmes for athletes.